Validation of a pictionary-based communication tool for assessing physiological needs and motivational states: the PAIN set - Proverbio, Alice Mado; Pischedda, Francesca (Frontiers in Cognition, 2023)
This Pictionary is suitable for communicating with individual unable to interact (locked-in syndrome, LIS) through the development of Brain Computer Interface (BCI) systems. It includes 60 validated, easy-to-understand illustrated plates depicting adults in various situations affecting their physiological or psychological state. The drawings are in color and represent persons of both sexes and various ethnicities. Twenty participants were interviewed to appropriately design the Pictionary. An additional group of 50 healthy adults (25 women and 25 men) aging 18–33 years was recruited to validate the pictogram corpus. Their schooling levels ranged from middle school to master's degrees. Participants were presented with five runs of randomly mixed pictograms illustrating 12 different motivational states, including primary and secondary needs, affective states, and somatosensory sensations (with five variants for each category). They had to precisely identify the motivational category illustrated (e.g., “Feeling pain” or “Being hungry”) while also providing information about its clarity and unambiguity on a Likert scale. Statistical analyses provided evidence of the strong communicative effectiveness of the illustrations (rated on average 2.7, on a 0 to 3 scale), with an accuracy of 98.4%. The PAIN set could be a valuable communication tool for individuals with LIS, as well as any clinical population lacking verbal communication skills. Its main purpose is to generate electrophysiological markers of internal mental states to be automatically classified by BCI systems.